Nanomedicine and chemotherapeutics drug delivery: challenges and opportunities. (7th February 2021) - Nezhadi, Sepideh; Saadat, Ebrahim; Handali, Somayeh; Dorkoosh, Farid
Abstract: Cancer is considered as one of the biggest threats to humans worldwide. Researchers suggest that tumour is not just a single mass, it comprises cancerous cells surrounded by noncancerous cells such as immune cells, adipocytes and cancer stem cells (CSCs) in the extracellular matrix (ECM) containing distinct components such as proteins, glycoproteins and enzymes; thus tumour microenvironment (TME) is partially complex. Multiple interactions happen in the dynamic microenvironment (ME) lead to an acidic, hypoxic and stiff ME that is considered as one of the major contributors to cancer progression and metastasis. Furthermore, TME involves in drug resistance mechanisms and affects enhanced permeability and retention (EPR) in tumours. In such a scenario, the first step to accomplish satisfying results is the identification and recognition of this ME. Then designing proper drug delivery systems can perform selectively towards cancerous cells. In this way, several targeting and stimuli/enzyme responsive drug delivery systems have been designed. More importantly, it is necessary to design a drug delivery system that can penetrate deeper into the tumours, efficiently and selectively. Various drug delivery systems such as exosomes and size-switchable nanocarriers (NCs) could decrease side effects and increase tumour treatment results by selective accumulation in tumours. In this review, TME features, current drug delivery approaches, challenges and promising strategies towards cancer treatment are discussed.